Aggregation potency and proinflammatory effects of SARS-CoV-2 proteins - Costa, Monica; Wang, Da-Wei; Zhao, Kai-Dong; Yuan, Lin; Krisko, Anita; Li, Jia-Yi; Outeiro, Tiago; Li, Wen (Scientific Reports, 2025)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is primarily known as a respiratory disease. The continued study of the disease has shown that long-term COVID-19 symptoms include persisting effects of the virus on the brain when the infection is over, possibly even leading to neurodegeneration. However, the exact mechanisms of nervous system damage induced by SARS-CoV-2 are still unclear. In this study, we focused on two possibly shared pathways of SARS-CoV-2-induced neural dysfunction and neurodegeneration: protein aggregation, which is associated with impaired protein clearance, and inflammatory responses, which involve a hyper-active immune status. We observed distinct expression and distribution patterns of ten SARS-CoV-2 proteins in the two cell lines, meanwhile forming aggregation puncta and inducing pro-inflammatory responses. We found that the ER stress was induced and that the autophagy-lysosome pathway was inhibited upon viral protein expression. Boosting autophagy function attenuated protein aggregation, suggesting that modulation of autophagy might be a valid strategy for inhibiting cytotoxic effects of SARS-CoV- 2 proteins. Our study provides potential explanations of SARS-CoV-2-induced cell damage, based on shared cellular mechanisms and furthermore, suggests that modulation of proteostasis may serve as therapeutic strategies for preventing long-lasting SARS-CoV-2 cytotoxic effects.
© 2025. The Author(s).
Keywords: Humans; SARS-CoV-2/metabolism; Autophagy; COVID-19/virology; Endoplasmic Reticulum Stress; Protein Aggregates; Viral Proteins/metabolism; Lysosomes/metabolism; Inflammation; Animals; Chlorocebus aethiops; Vero Cells; Cell Line